Eribulin mesilate versus vinorelbine in women with locally recurrent or metastatic breast cancer: A randomised clinical trial. (May 2019) - Yuan, Peng; Hu, Xichun; Sun, Tao; Li, Wei; Zhang, Qingyuan; Cui, Shude; Cheng, Ying; Ouyang, Quchang; Wang, Xiaojia; Chen, Zhendong; Hiraiwa, Masahide; Saito, Kenichi; et al.
Abstract: Introduction: The objective of this study was to evaluate the efficacy and safety of eribulin monotherapy, relative to vinorelbine, in Chinese women with locally recurrent/metastatic breast cancer (MBC). Methods: This phase III open-label, randomised, parallel-group, multicentre clinical trial enrolled patients with locally recurrent or MBC who had had 2–5 prior chemotherapy regimens, including an anthracycline and taxane) from September 26, 2013, to May 19, 2015. Women were randomised 1:1 to receive eribulin (1.4 mg/m 2, intravenously, on day 1 and day 8) or vinorelbine (25 mg/m 2, intravenously, on day 1, day 8 and day 15) every 21 days. The primary end-point was progression-free survival (PFS). Secondary end-points included objective response rate (ORR), duration of response and overall survival (OS). Results: Five hundred thirty women were randomised to receive eribulin (n = 264) or vinorelbine (n = 266). Improvement in PFS was observed with eribulin compared with vinorelbine (hazard ratio [HR]: 0.80, 95% confidence interval [CI]: 0.65–0.98, P = 0.036); median PFS was 2.8 months in both treatment arms. The median OS was 13.4 months with eribulin and 12.5 months with vinorelbine (HR: 1.03, 95% CI: 0.80–1.31, P = 0.838). The ORR was 30.7% (95% CI: 25.2%–36.6%) with eribulin and 16.9% (95% CI: 12.6%–22.0%) with vinorelbine (P < 0.001). Treatment-emergent adverse events leading to treatment discontinuation were less frequent with eribulin (7.2%) than with vinorelbine (14.0%). Conclusions: Eribulin achieved statistically significantly superior PFS (and response rate) compared with vinorelbine in previously treated women with locally recurrent or MBC. Eribulin appeared to be better tolerated than vinorelbine, with no new safety signals observed. Trial registration: National Institutes of HealthClinicalTrials.gov registry, NCT02225470. Registered 05 August 2014- Retrospectively registered.https://clinicaltrials.gov/ct2/show/NCT02225470?term=NCT02225470&rank=1 . Highlights: A study of eribulin versus vinorelbine in Chinese women with metastatic breast cancer. Significant improvements in progression-free survival and objective response rate were seen with eribulin versus vinorelbine. Toxicity profiles for both were as expected, with no new safety signals observed.